2017
DOI: 10.3390/e19090498
|View full text |Cite
|
Sign up to set email alerts
|

Second Law Analysis for Couple Stress Fluid Flow through a Porous Medium with Constant Heat Flux

Abstract: Abstract:In the present work, entropy generation in the flow and heat transfer of couple stress fluid through an infinite inclined channel embedded in a saturated porous medium is presented. Due to the channel geometry, the asymmetrical slip conditions are imposed on the channel walls. The upper wall of the channel is subjected to a constant heat flux while the lower wall is insulated. The equations governing the fluid flow are formulated, non-dimensionalized and solved by using the Adomian decomposition metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…We collected 12 papers in this special issue, covering both engineering applications [8][9][10][11][12] and fundamental studies [13][14][15][16][17][18][19] with respect to CFD of flow and heat transfer problems and interpretation of the CFD results with the SLA.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…We collected 12 papers in this special issue, covering both engineering applications [8][9][10][11][12] and fundamental studies [13][14][15][16][17][18][19] with respect to CFD of flow and heat transfer problems and interpretation of the CFD results with the SLA.…”
mentioning
confidence: 99%
“…The SLA was also intensively applied to fundamental studies, such as convective heat transfer problems [13][14][15][16][17][18]. Four papers among these studies are about forced convection: Ji et al [13] analyzed the entropy generation of fully-turbulent convective heat transfer of nano-fluids in a circular tube according to their RANS results.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al have investigated second law analysis of turbulent fully‐developed heat transfer flow in inward helically corrugated tubes. Adesanya et al have reported second law analysis of couple stress fluid flow through a parallel inclined channel. Reddy et al have discovered entropy generation of Casson fluid flow past a vertical cylinder and used finite difference method for solution.…”
Section: Introductionmentioning
confidence: 99%